Deficiency of intestinal mucin‐2 ameliorates experimental alcoholic liver disease in mice12. Issue 1 (27th May 2013) - Hartmann, Phillipp; Chen, Peng; Wang, Hui J.; Wang, Lirui; McCole, Declan F.; Brandl, Katharina; Stärkel, Peter; Belzer, Clara; Hellerbrand, Claus; Tsukamoto, Hidekazu; Ho, Samuel B.; Schnabl, Bernd
Abstract The intestinal mucus layer protects the epithelium from noxious agents, viruses, and pathogenic bacteria present in the gastrointestinal tract. It is composed of mucins, predominantly mucin (Muc) 2, secreted by goblet cells of the intestine. Experimental alcoholic liver disease requires translocation of bacterial products across the intestinal barrier into the systemic circulation, which induces an inflammatory response in the liver and contributes to steatohepatitis. We investigated the roles of the intestinal mucus layer, and in particular Muc2, in development of experimental alcohol‐associated liver disease in mice. We studied experimental alcohol‐induced liver disease, induced by the Tsukamoto‐French method (which involves continuous intragastric feeding of an isocaloric diet or alcohol) in wild‐type and Muc2−/− mice. Muc2−/− mice showed less alcohol‐induced liver injury and steatosis than developed in wild‐type mice. Most notably, Muc2−/− mice had significantly lower plasma levels of lipopolysaccharide than wild‐type mice after alcohol feeding. In contrast to wild‐type mice, Muc2−/− mice were protected from alcohol‐associated microbiome changes that are dependent on intestinal mucins. The antimicrobial proteins regenerating islet‐derived 3 beta and gamma were expressed at significantly higher levels in the jejunum of Muc2−/− mice fed the isocaloric diet or alcohol compared with wild‐type mice. Consequently, Muc2−/− mice showed increased killing of commensal bacteria and prevented intestinal bacterial overgrowth. Conclusion: Muc2−/− mice are protected from intestinal bacterial overgrowth and dysbiosis in response to alcohol feeding. Subsequently, lower amounts of bacterial products such as endotoxin translocate into the systemic circulation, decreasing liver disease. (HEPATOLOGY 2013;)